Passive income lures people to get-rich-quick schemes - Daily Express, (KK) (Daily Express (KK), 2016)
KOTA BARU: Earning passive income without having to lift a finger has caused many to be easily deceived into joining get-rich-quick schemes without thinking of the risks that await them.